2020
DOI: 10.1080/17482631.2020.1783859
|View full text |Cite
|
Sign up to set email alerts
|

Defining and implementing social integration: a case study of school leaders’ and practitioners’ work with newly arrived im/migrant and refugee students

Abstract: Purpose: This study probes educational leaders and practitioner's views about social integration with newly arrived im/migrant and refugee students. A sociological perspective of education is used in conjunction with a thematic analysis of neoliberal approaches to diversity management and its social implications for the health and well-being for im/migrant students.Methods: An interview study with 15 educational leaders and practitioners in schools and recreational centres was carried out. Thereof, seven depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…17 Réussite du PAE-Statistiques, Radius, field document. 18 Social downward (Leo 2022;Lundberg 2020;Çelik and ˙Içduygu 2019) is one of them, concerning both the decrease in the socio-economic status of the person, and the fact that he or she has to start studying again, often already being qualified because of the university training courses completed in the country of origin.…”
Section: Discussionmentioning
confidence: 99%
“…17 Réussite du PAE-Statistiques, Radius, field document. 18 Social downward (Leo 2022;Lundberg 2020;Çelik and ˙Içduygu 2019) is one of them, concerning both the decrease in the socio-economic status of the person, and the fact that he or she has to start studying again, often already being qualified because of the university training courses completed in the country of origin.…”
Section: Discussionmentioning
confidence: 99%
“…A productive activity refers to any type of paid or unpaid activity that produces such goods or services of value. 23 Previous studies have broadly identified productive activities as one of the types of activity: employment, [24][25][26] education, 27 and volunteer work. 24,26 The varied productive activities can be determined by an individual's characteristics-such as age, gender, education, and health status.…”
Section: Productive Activitiesmentioning
confidence: 99%
“…Many children seek refuge or migrate to European countries, often arriving unaccompanied, traumatized by the violence they faced and the loss of their beloved ones. Once arrived in Europe, the struggle goes on, facing difficulties with integration in school (Crul et al, 2019), peer community (Daniel et al, 2020), and their broader social circle (Lundberg, 2020). For example in Greece, one of the countries that has been receiving hundreds of thousands of refugees over the past years, it is clearly evident that refugees remain socially excluded, despite the various humanitarian programs that have been developed to support people's lives (Bareka et al, 2019).…”
Section: Introductionmentioning
confidence: 99%